Characterisation of fractured particulate reinforced composite. (29th December 2014) - Ahmed, Waleed K.; Teng, Hong
The objective of this analysis is to predict the effective stiffness of a particulate–reinforced composite through finite element method (FEM) as a powerful tool. Basically, the investigation covers the assessment of two specific cases. In the first case, a perfect particulate reinforcement is considered, where the particles are considered as fully intact. In the second case, the particles are proposed to be fully fractured. Linear elastic, two–dimensional (2D) finite element analysis (FEA) is adopted in the analysis. The particle's stiffness is considered as a substantial parameter in the analysis. Moreover, various particle volume fractions are taken into account to discover their influence on the effective Young's modulus for the studied cases. The results are compared with analogous three–dimensional (3D) results for particulate composites and discussed.